Sustainable Community Service Initiatives for Environmental Cleanliness and Coral Reef Restoration on Gili Tangkong - Herman; Hamzah, Muhammad Ilham; Royanow, Achlan Fahlevi; Satrio, Muhammad; Rizkiyah, Putri; Fahmi, Saiful (Abdi Wisata: Jurnal Pengabdian Kepada Masyarakat, 2024)
Small islands in Lombok, such as Gili Tangkong, have immense tourism potential with their natural beauty and rich marine coral ecosystems. Nonetheless, large numbers of tourists and insufficient environmental management have contributed to coral reef damage and a decline in the quality of cleanliness. This community service initiative, which involves both tourists and local people, strives to increase environmental sustainability by transplanting coral reefs, planting trees, and cleaning beaches. The activities lasted two days and involved lecturers, students, tourists, and members of the neighboring community. The findings revealed major benefits in the marine habitat, avoidance of coastal erosion, and greater environmental consciousness among tourists and locals. The challenges include delivering technical information, selecting proper locations, and effectively managing waste. The goal of this program is to set a positive example for environmental conservation and enhance the appeal of sustainable tourism in Gili Tangkong. Keywords: